Investigation of gas natural separation process unsteady features by means of an experimental rig and mathematical modeling - V. A. Ivanov; V. S. Verbitsky; R. A. Khabibullin; K. A. Goridko; E. I. Nikonov (Georesursy)
Natural gas separation is an important process in wells equipped with electric submersible pumps (ESP) that affects the efficiency of the "wellbore-pump-tubing" system. Nowadays, the amount of knowledge about this process requires critical analysis and further improvement. The paper presents the results of studying the unsteady features of the process of separation of gas bubbles into the annular space in the near-intake domain of the well model with conditionally radial inlet. The results of the experimental bench tests, as well as the results of numerical simulation in dynamic multiphase flow simulator are analyzed. The experiments were carried out on a test rig with the inner diameter of the casing model 80 mm and the outer diameter of the intake module 64 mm, taking into account the possibility of measuring liquid and gas flow rates, as well as high-speed video recording of the processes occurring in the near-intake domain of the well model. Unsteady features of gas-liquid mixtures flow with the help of video frames in the near-intake domain for model mixtures “Water-Air” and “Water-Surfactant-Air” are shown. It is revealed that at small time intervals (<1 s) the regimes with slug-churn flow pattern are characterized by significant nonstationarity. The results of numerical simulation indicate that such unsteady behavior can lead to oscillatory operation of the well and ESP.On the basis of critical analysis of the obtained research results the following promising directions are formulated: a study of theoretical basis of separation in the near-intake domain of a well; field and bench experiments; a numerical modeling of gas natural separation into the annular space of a well equipped with ESP.